The International Effects of Government Spending Composition - Ganelli, Giovanni (IMF Working Papers; Working Paper ;, 2005)
This paper helps resolve a paradox in the literature, noticed by Alesina and Perotti (1995), which is that, although government employment is an important component of public spending, the debate on the effects of fiscal policy focuses almost exclusively on shocks to non-wage government consumption. We incorporate the distinction between spending for government employment and spending for non-wage government consumption in a "new open economy macroeconomics" model. Our results show that a permanent reduction in public employment in one country reduces relative private consumption and appreciates the domestic exchange rate if it is matched by a reduction in taxes. When the reduction in public employment is used to finance increased non-wage government consumption, the macroeconomic effects results are ambiguous, and are affected by the initial level of the public wage bill.